Two roads home : Hitler, Stalin, and the miraculous survival of my family - Finkelstein, Daniel, 1962- (Doubleday, 2023)
"An epic and beautifully written World War II family history that spans Europe, telling of two happy families uprooted by war, their incredible suffering in Hitler's and Stalin's camps, and the near-miraculous survival and rescue of the author's parents who met after the war. Daniel Finkelstein's grandfather Alfred Wiener was a German Jewish intellectual leader who tolled an early warning of the impending Holocaust and became an archivist of Nazi crimes. He relocated his family to safety in Amsterdam, where they became close with Anne Frank's family. But they were eventually separated, and Daniel's mother Mirjam was sent to Bergen-Belsen with her mother and sisters while Alfred worked feverishly to free them. Finkelstein's father, Ludwik, grew up in a prosperous Jewish family in Poland where his father was a patriotic hero of the Great War. But when Stalin took control, Finkelstein's grandfather was deported to Siberia, while Ludwik and his mother were sent to Kazahkstan, where they barely survived freezing winters and harrowing forced labor conditions. Two Roads Home is a page-turning account of ingenuity, bravery and the almost unbelievable coincidences that brought Daniel's parents together. The story features secret archives, forgery and theft, and sweeps across Europe to show the expanse of the war. Moving, engrossing and inspiring, Two Roads Home will profoundly touch all who read it"--